Analisis Penerapan Internasional Ship and Port Facility Security (ISPS) Code terhadap Peningkatan Efektivitas Keamanan di dermaga Internasional Bulk Liquid (IBL) Pelabuhan Gresik - Bayu Aditya Nugroho; Romanda Annas Amrullah; Ita Masita; Elly Kusumawati (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Indonesia's strategic ports face rising maritime threats like piracy and terrorism, necessitating effective ISPS Code implementation. This study analyzes the application of ISPS Code (X) and its impact on security effectiveness (Y) at the International Bulk Liquid (IBL) Terminal, Gresik Port. Employing a quantitative descriptive-explanatory approach, data were collected via Likert-scale questionnaires from 50 purposive respondents (security personnel, PFSO, operators) during January-June 2025, supported by observations and secondary documents. Instruments were validated (r-hitung > 0.235; sig. <0.05) and reliable (Cronbach's α X=0.848, Y=0.804), analyzed using simple linear regression in SPSS. Results show excellent ISPS implementation (mean 4.46) and security effectiveness (mean 4.68), with significant positive influence (t=11.852 > 1.677; sig=0.000; R²=0.745; Y=17.071+0.641X). In conclusion, ISPS Code substantially enhances port security, recommending intensified training and technology integration.